Reforma de ensino de 2º grau na conjuntura histórica da ditadura civil-militar (1964-1985): um estudo sobre as representações discursivas da lei nº 5692/71 - Santos, Auristela Rodrigues dos (2018)
This dissertation paper, entitled Professional Education Reform in the Historical Juncture of the Brazilian Civil-military Dictatorship (1964-1985): A study of the discursive representations of Law n. 5692/71, intended to develop a study of the professional education reform, promulgated in the context of the Civil-military dictatorship (1964-1985), aiming to understand the discursive representations of Law n. 5692/71, considering the legal documents and the memories of people who experienced the professional education in the dictatorial scenario. It is a qualitative research, based on the concepts of history, memory, and representation by Roger Chartier (1991). The written and oral sources made possible a hybrid dialogue, in which the Oral history methodology was essential to provide a discussion of the individual and collective memory of this event and to dialogue with the existing documents, arousing reflections about the reform, its proposal and representations. Among the authors studied, we can mention: Germano (2011); Halbwachs (2006); Chartier (1991; 2016); Thompson (1992), among others. It is emphasized that the changes to the National Education Guidelines and Framework Law (Lei de Diretrizes e Bases da Educação - LDB) reached the whole nation, and that the associated practices and ideologies were in accordance with the anti-democratic government experienced by the Brazilian society then. In the current study, we realized that the professional education reform was based on the Human Capital Theory, with a technicist proposal that guided the character of the terminality attributed to it. We emphasize the importance of the testimonies of those who experienced this education reform, making it possible to establish a dialogue between the legal documents and the versions of the participants.